Сatastrophic model of destruction and experimental research of polymer materials irradiated by electrons - Kupchishin, A.I.; Muradov, A.D.; Taipova, B.G.; Voronova, N.A. (Publishing House of the KarSU named after E.A.Buketov, 2009)
The paper is devoted to research of physical and mechanical properties of metallized polymer composites based on polyimide and silver irradiated by electrons up to different integral doses and temperature. General principles of operation of upgraded computerized test setup have been described. Obtained experimental data have been explained within catastrophic exponential model of destruction.
Keywords: metallized polymer composites; model of destruction; electrical properties; irradiation dose